Tacrolimus Increases the Effectiveness of Itraconazole and Fluconazole against Sporothrix spp. - Borba-Santos, Luana P.; Reis de Sá, Leandro F.; Ramos, Juliene A.; Rodrigues, Anderson M.; de Camargo, Zoilo P.; Rozental, Sonia; Ferreira-Pereira, Antonio (Frontiers in Microbiology, 2017)
Calcineurin inhibitors - such as the clinically used drug tacrolimus - are active against important fungal pathogens, particularly when combined with azoles. However, tacrolimus has not been tested against sporotrichosis, an endemic subcutaneous mycosis with worldwide distribution. Here, we evaluated the activity of tacrolimus and cyclosporine A in vitro - as monotherapy and in combination with itraconazole or fluconazole - against yeasts of Sporothrix brasiliensis and S. schenckii, the main sporotrichosis agents in Brazil. We also analyzed the effect of tacrolimus treatment on intracellular neutral lipid levels, which typically increase after azole treatment. Tacrolimus inhibited the growth of yeasts from S. brasiliensis and S. schenckii reference isolates, with minimum inhibitory concentration (MIC) values (required for ≥ 50% growth inhibition) of 1 and 2 mg/L, respectively. Importantly, the combination of tacrolimus and azoles exhibited high synergy towards reference Sporothrix isolates. Tacrolimus combined with itraconazole significantly increased neutral lipid accumulation in S. brasiliensis, but not in S. schenckii. Clinical isolates of S. brasiliensis and S. schenckii were more sensitive to tacrolimus as monotherapy than feline-borne isolates, however synergy between tacrolimus and azoles was only observed for feline-borne isolates. Cyclosporine A was effective against S. brasiliensis and S. schenckii as monotherapy (MIC = 1 mg/L), but exhibited no synergy with itraconazole and fluconazole. We conclude that tacrolimus has promising antifungal activity against sporotrichosis agents, and also increases the activity of the current anti-sporotrichosis therapy (itraconazole and fluconazole) in combination assays against S. brasiliensis feline-borne isolates.